Oropharyngeal Dysphagia in Neurodegenerative Disease - WALSHE, MARGARET (My University, 2014)
Oropharyngeal dysphagia is frequent in neurodegenerative diseases with medical, social and psychological effects. There is a paucity of evidence on the frequency, nature and course of oropharyngeal dysphagia in these conditions. The nature and characteristics of the swallowing disorder can vary according to the neurological condition, the severity of the underlying disease and other patient comorbidities. Early detection of oropharyngeal dysphagia is important to decrease aspiration risk and limit health and social consequences. Management options vary from compensatory and rehabilitation exercise approaches with evolving evidence on how best to manage the condition. Many individuals require enteral tube feeding in the later stages of the disease. This paper examines oropharyngeal dysphagia in some of the primary neurodegenerative diseases, exploring current management options highlighting directions for research and clinical practice.
PUBLISHED
Keywords: Deglutition Disorders; Neurodegenerative disease; Review